Thinking with type : a critical guide for designers, writers, editors, & students - Lupton, Ellen (New York : Princeton Architectural Press, 2010)
Our all-time best selling book is now available in a revised and expanded second edition. Thinking with Type is the definitive guide to using typography in visual communication, from the printed page to the computer screen. This revised edition includes forty-eight pages of new content, including the latest information on style sheets for print and the web, the use of ornaments and captions, lining and non-lining numerals, the use of small caps and enlarged capitals, as well as information on captions, font licensing, mixing typefaces, and hand lettering. Throughout the book, visual examples show how to be inventive within systems of typographic form--what the rules are and how to break them. Thinking with Type is a type book for everyone: designers, writers, editors, students, and anyone else who works with words. --Publisher description.
Letter. Humanism and the body ; Enlightenment and abstraction ; Monster fonts ; Reform and revolution ; Type as program ; Type as narrative ; Back to work ; Anatomy ; Size; Scale ; Type classification ; Type families ; Superfamilies ; Capitals and small capitals ; Mixing typefaces ; Numerals ; Punctuation ; Ornaments ; Lettering ; Logotypes and branding ; Typefaces on screen ; Bitmap typefaces ; Typeface design ; Exercise : Modular letterforms ; Font formats ; Font licensing -- Text. Errors and ownership ; Spacing ; Linearity ; Birth of the user ; Kerning ; Tracking ; Exercise : space and meaning ; Line spacing ; Alignment ; Exercise : alignment ; Vertical text ; Enlarged capitals ; Marking paragraphs ; Captions ; Hierarchy ; Exercise : hierarchy ; Exercise : long lists -- Grid. Gris as frame ; Dividing space ; Grid as program ; Grid as table ; Return to universals ; Golden section ; Single-column grid ; Multicolumn grid ; Modular grid ; Exercise : modular grid ; Data tables ; Exercise : data tables -- Appendix. Spaces and punctuation ; Editing ; Editing hard copy ; Editing soft copy ; Proofreading ; Free advice.
Includes bibliographical references and index.
Keywords: Graphic design (Typography); Type and type-founding.